“Flash” Annealing in a Cold-Rolled Low Carbon Steel Alloyed with Cr, Mn, Mo, and Nb: Part Ii—Anisothermal Recrystallization and Transformation Textures - Castro-Cerda, F (Wiley-VCH Verlag, 2019)
The aim of the present investigation is to study the microstructure and texture evolution in a cold-rolled low carbon steel subjected to continuous heating and subsequent quenching. Peak-annealing and quenching experiments are carried out at different temperatures at three heating rates (10, 400, and 1000 °C s−1). The texture evolution in ferrite and martensite is analyzed separately via Electron Backscattered Diffraction (EBSD) measurements. It is observed that the recrystallization is virtually completed at 771 °C in samples heated at 10 °C s−1. Conversely, the recrystallization is suppressed in samples heated at rates ≥400 °C s−1. In samples heated at 10 °C s−1, the ferrite texture evolves according to the well-known recrystallization behavior, showing a maximum in {113}<110> components, whereas in samples heated at rates ≥400 °C s−1, the texture is similar to the one of the cold-rolled material. It is concluded that the texture evolution in martensite is strongly dependent on the evolution of recrystallization textures in ferrite. A particular grain substructure product of the interaction between the recrystallization of ferrite and massive austenite formation is observed after heating at rates ≥400 °C s−1. However, this substructure seems to have effect neither on the textures of ferrite nor on the work hardening behavior. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim